Moving between material and conceptual structure: Developing a card-based method to support design for learning. (September 2019) - Yeoman, Pippa; Carvalho, Lucila
Abstract : This article traces the development of a card-based method that weaves the conceptual structure of learning theories into the material practises of those involved in design for learning. Inspired by design thinking and design anthropology, this method also draws on the literature of education and the learning sciences and it is the embodiment of the ACAD framework. Developed in response to challenges encountered communicating research findings to heterogenous design teams, the ACAD cards have been used in (re)designing curricula and facilities in school and university settings in Australia and New Zealand. We argue this method supports educational innovation through abductive sensemaking or design synthesis and has the potential to support the reconciliation of material and conceptual structure in other contexts. Highlights: The (re)design of environments for learning is a major trend shaping education. Educational design is ill-equipped to connect conceptual and material structure. Designing for learning requires deep knowledge about how humans learn. We present the development of a card-based method to support heterogenous teams. This method has broad application in environments undergoing change.